Decreased circulating omega-3 fatty acids increase the risk of myocardial infarction: a two-sample Mendelian randomization study - Wang, Wei; Yang, Linfei; Zhang, Jing; Xiang, Haiyun (Frontiers in Cardiovascular Medicine, 2024)
Background Many studies have shown that omega-3 fatty acids may play critical roles in cardiovascular diseases. Myocardial infarction (MI) typically results from a thrombotic occlusion of a coronary artery leading to myocardial ischemia. Thus, this study aims to examine the association between omega-3 fatty acids and MI. Methods A two-sample Mendelian randomization study was used to explore the causal relationship between circulating omega-3 fatty acids and the risk of MI performed by MR-Egger regression, inverse-variance weighted (IVW), weighted median, and weighted mode. Results Five single-nucleotide polymorphisms strongly related to circulating omega-3 fatty acids were selected as instrumental variables from a published genome-wide association study (GWAS) meta-analysis including 13,544 subjects. We extracted summary data for the risk of MI from another GWAS meta-analysis including 171,875 individuals (43,676 cases and 128,199 controls). The genetically predicted lower circulating omega-3 increased the risk of myocardial infarction showed by the results of IVW [odds ratio (OR) = 1.224, 95% CI = 1.045–1.433, P = 0.012], weighted median method (OR = 1.171, 95% CI = 1.042–1.315, P = 0.008), and weighted mode (OR = 1.149, 95% CI = 1.002–1.317, P = 0.117), although the result of MR-Egger was not significant (OR = 0.950, 95% CI = 0.513–1.760, P = 0.880) with a wider confidence interval. Conclusion The findings from our Mendelian randomization analysis suggest that the association between omega-3 fatty acid levels and MI is likely causal.